2006 IEEE International Symposium on Information Theory 2006
DOI: 10.1109/isit.2006.261776
|View full text |Cite
|
Sign up to set email alerts
|

Partially-Coherent Distributed Space-Time Codes with Differential Encoder and Decoder

Abstract: Abstract-Distributed space-time coding is a means of achieving diversity through cooperative communication in a wireless relay network. In this paper, we consider a transmission protocol that follows a two-stage model: transmission from source to relays in the first stage, followed by a simple relaying technique from relays to destination. The relays transmit a vector, which is a transformation of the received vector by a relay-specific unitary transformation. We assume that the relays do not have any channel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 13 publications
0
31
0
Order By: Relevance
“…where and denote the real and imaginary parts, we obtain that (14) Equating to zero, we obtain that (15) It follows from (15) that should be chosen as one of the eigenvectors of the matrix and is the corresponding eigenvalue. Multiplying both sides of (15) with yields (16) where in the last equality we have used the constraint in (12).…”
Section: Power Minimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…where and denote the real and imaginary parts, we obtain that (14) Equating to zero, we obtain that (15) It follows from (15) that should be chosen as one of the eigenvectors of the matrix and is the corresponding eigenvalue. Multiplying both sides of (15) with yields (16) where in the last equality we have used the constraint in (12).…”
Section: Power Minimizationmentioning
confidence: 99%
“…Of all these schemes, the amplify-and-forward approach, due to its simplicity, is of particular interest. Recently, the amplify-and-forward approach has been extended to develop space-time coding strategies for relay networks, thereby opening a new research avenue called distributed space-time coding [9]- [15]. While the aforementioned cooperative approaches assume different levels of CSI availability in the network, they all share the common assumption that the relay nodes operate at their maximum allowable power.…”
Section: Introductionmentioning
confidence: 99%
“…Obtaining the knowledge of the fading coefficients between the users at the destination requires additional resources. To solve this problem, in [2], Kiran et al have proposed a differential encoding/decoding setup for cooperative wireless networks that does not require the knowledge of fading coefficients between the users at the destination. Such codes were named as partially coherent distributed space-time codes in [2].…”
mentioning
confidence: 99%
“…To solve this problem, in [2], Kiran et al have proposed a differential encoding/decoding setup for cooperative wireless networks that does not require the knowledge of fading coefficients between the users at the destination. Such codes were named as partially coherent distributed space-time codes in [2]. In a recent work [4], it has been shown that the same strategy of [2] offers full diversity with a suboptimal receiver that does not require the knowledge of any of the fading coefficients.…”
mentioning
confidence: 99%
See 1 more Smart Citation